2007
DOI: 10.1016/s0001-2092(07)60147-1
|View full text |Cite
|
Sign up to set email alerts
|

2.2 Pediatric Medication Errors in the Postanesthesia Care Unit: Analysis of MEDMARX Data

Abstract: Medication errors involving pediatric patients in the postanesthesia care unit may occur as frequently as one in every 20 medication orders and are more likely to cause harm when compared to medication errors in the overall population. Researchers examined six years of records from the MEDMARX database and used consecutive nonprobability sampling and descriptive statistics to compare medication errors in the pediatric data set to those occurring in the total population data set. Nineteen different causes of er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 15 publications
0
20
0
3
Order By: Relevance
“…Medications for children often come in liquid form, and multiple medication formulations may lead to dosing errors (Kaushal et al, 2007;Kozer et al, 2006), which are the most commonly reported errors in pediatric care (Kozer et al, 2006). Children are often unable to adequately communicate when they are experiencing an adverse effect, and their ability to buffer medication errors is significantly less than adults (Payne, Smith, Newkirk, & Hicks, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Medications for children often come in liquid form, and multiple medication formulations may lead to dosing errors (Kaushal et al, 2007;Kozer et al, 2006), which are the most commonly reported errors in pediatric care (Kozer et al, 2006). Children are often unable to adequately communicate when they are experiencing an adverse effect, and their ability to buffer medication errors is significantly less than adults (Payne, Smith, Newkirk, & Hicks, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Medical errors can usually be traced back to manual transmission of information across different functional units of the hospital (e.g., information from the preoperative unit to the operating room to the recovery room to regular wards), manual calculations of doses, and unmonitored clinical interventions (Payne et al 2007). It is here that automation of information capture and transmission between agents and across the different functional units of the hospital can reduce the rate of medical errors because they enable the automation of the Information Systems Research 22(3), pp.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 Literatürde ilacın hazırlanması ve uygulanmasına ilişkin belirlenen hatalar; ilacı yanlış çözücü ile sulandırma, son kullanma tarihi geç-miş ilaç kullanma, yanlış yolla ilaç verme, yanlış teknikle ilaç verme, yanlış zamanda ilaç verme, ilaç dozlarını atlama, yanlış intravenöz sıvı kullanma, ilacın yanlış hızla verilmesi, yanlış kişiye ilaç verme, hekim istemlerinin alınmasında hata yapma, ilaç dozunun yanlış hesaplanması, yanlış dozda ilaç verme, enteral beslenme solüsyonunun santral venöz kateterden verilmesi, ilaç-ilaç, ilaç-besin ve ilaç-intravenöz sıvı etkileşimleri ve verilen ilacın kayıt edilmemesidir. 2,9,10,14 Yapılan bu ilaç hatalarını etkileyen faktörler ise yoğun bakım ve acil serviste çalışma ortamının karmaşıklığı, aşırı iş yükü, yorgunluk, akut ve kronik uyku yoksunluğu, eleman eksikliği, ilacı hazırlarken ortamda dikkati dağıtan faktörlerin olması, elemanların deneyimsizliği, ünitede hasta sayısının fazla olması, bilgi yetersizliği, yetersiz iletişim, yetersiz kayıt, hemşire/hasta oranı, nöbet değişiminde yetersiz bilgi paylaşımı, ünitede uygulanan ilaç miktarı, hastanın ya da ilacın yeni olması, vücut ağırlığına göre doz hesaplamasının gerekmesi, çocukların ilaç alımı konusunda ebeveynlerine bağımlı olmaları ve iletişim kurmadaki yetersizlikleri, ilaç kutuları üze-rindeki yazıların küçük olması nedeniyle okunma güçlüğü ve uygulanan ilacın etkisinin gözlenme-mesidir.…”
Section: ) Hemşi̇re Kaynakli İlaç Hatalariunclassified
“…2,9,10,14 Yapılan bu ilaç hatalarını etkileyen faktörler ise yoğun bakım ve acil serviste çalışma ortamının karmaşıklığı, aşırı iş yükü, yorgunluk, akut ve kronik uyku yoksunluğu, eleman eksikliği, ilacı hazırlarken ortamda dikkati dağıtan faktörlerin olması, elemanların deneyimsizliği, ünitede hasta sayısının fazla olması, bilgi yetersizliği, yetersiz iletişim, yetersiz kayıt, hemşire/hasta oranı, nöbet değişiminde yetersiz bilgi paylaşımı, ünitede uygulanan ilaç miktarı, hastanın ya da ilacın yeni olması, vücut ağırlığına göre doz hesaplamasının gerekmesi, çocukların ilaç alımı konusunda ebeveynlerine bağımlı olmaları ve iletişim kurmadaki yetersizlikleri, ilaç kutuları üze-rindeki yazıların küçük olması nedeniyle okunma güçlüğü ve uygulanan ilacın etkisinin gözlenme-mesidir. 16,18,22,[25][26][27]28 Mayo ve Duncan'ın yaptıkları çalışmada, bir servis hemşiresinin zamanının %40'ını ilaç uygulamaları ile geçirdiği ve bu zaman dilimi içinde 50'den fazla ilaç verebildiği belirlenmiştir. 29 Amerikan Hemşireler Birliği'nin yaptığı bir çalışmada, fazla çalışma ve haftalık toplam çalışma süresinin, hataları önemli ölçüde etkilediği belirlenmiştir.…”
Section: ) Hemşi̇re Kaynakli İlaç Hatalariunclassified